2021
DOI: 10.18632/aging.203296
|View full text |Cite
|
Sign up to set email alerts
|

ZC3HAV1 promotes the proliferation and metastasis via regulating KRAS in pancreatic cancer

Abstract: Proliferation and metastasis are important malignant features of pancreatic cancer (PC), but the underlying molecular mechanism is unclear. ZC3HAV1, a PARP family member of proteins-enzymes, has been considered to play a significant part in a variety of biological processes. Nonetheless, the functions of ZC3HAV1 in developing PC are still unknown. This research aims to explore the biological function and the expression of ZC3HAV1 shown in PC. In our study, PCR analysis suggested that ZC3HAV1 was expressed at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…EPRS was reported as a critical regulator of cell proliferation and estrogen signaling in ER + breast cancer [ 109 ] and has also been implicated as a potential treatment target for basal-like breast cancer [ 92 ]. ZC3HAV1, a PARP family enzyme, promotes proliferation and metastasis by regulating KRAS in pancreatic cancer [ 110 ] and is involved in facilitating DNA repair and promoting tumorigenesis in breast cancer [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…EPRS was reported as a critical regulator of cell proliferation and estrogen signaling in ER + breast cancer [ 109 ] and has also been implicated as a potential treatment target for basal-like breast cancer [ 92 ]. ZC3HAV1, a PARP family enzyme, promotes proliferation and metastasis by regulating KRAS in pancreatic cancer [ 110 ] and is involved in facilitating DNA repair and promoting tumorigenesis in breast cancer [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a member of the MAPK family, ERK1/2 transduces extracellular signals to intracellular signaling cascades, thereby regulating cell behaviors, including cell proliferation and differentiation [ 48 ]. Numerous studies have shown that the ERK/MAPK signaling pathway has crucial roles in tumorigenesis and metastasis [ 49 , 50 ]. HOXC6 has been shown to facilitate the proliferation and migration of glioblastoma cells by activating the ERK/MAPK signaling pathway [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…ZC3HAV1 (zinc finger CCCH-type antiviral protein 1), also known as PPAR13 [poly (ADP-ribose) polymerase-13] and ZAP (zinc-finger antiviral protein), is a PARP family member of RNA-binding proteins and has important functions in the cellular response to stress [ 41 ]. Studies have shown that it increases cell sensitivity to apoptosis [ 42 ], participates in facilitating DNA repair and promoting tumorigenesis of breast cancer [ 43 ], and facilitates metastasis and proliferation in pancreatic cancer [ 44 ], suggesting that it can be involved in malignant transformation and the development of cancer.…”
Section: Discussionmentioning
confidence: 99%